DYNAMICS OF HEALTH INDICATORS OF THE POPULATION OF THE REPUBLIC OF KARAKALPAKSTAN - Tadjibaeva M.K (International Journal of Innovations in Engineering Research and Technology, 2021)
The article is devoted to the study of the spatio-temporal dynamics of the health indicators of the population living in the region. It has been established that the influence of environmental factors in all cases is complex. A quantitative relationship was found between the complex of environmental factors and the degree of severity of its components and the state of health of the Republic of Karakalpakstan population.